The Effect of Liquidity and Profitability on Firm Value at PT Adhi Karya (SOE) Public Listed Company During 2012–2023 - Lubis, Iman; Feria Marsha Hena (Yayasan Pendidikan Penelitian Pengabdian Al-amsi, 2025)
This study revisits the relevance of liquidity and profitability as financial indicators of firm value in the context of a state-owned enterprise (SOE). Focusing on PT Adhi Karya (Persero) Tbk, a publicly listed construction SOE in Indonesia, the research covers the 2012–2023 period using a longitudinal approach. Liquidity is proxied by the Current Ratio (CR), profitability by Return on Assets (ROA), and firm value by the Price to Earnings Ratio (PER). Data were obtained from audited financial statements and analyzed using multiple linear regression. Results show that CR and ROA have no significant partial or simultaneous effect on PER. These findings suggest that conventional financial ratios may not fully capture market valuation in SOEs, where performance is shaped by both commercial and public-policy objectives. This study contributes to understanding the limitations of traditional valuation models in politically influenced firms.